Pembelajaran Daring PJOK Pada Masa Pandemi Covid-19: Studi Kasus di SMAN se-Surabaya - Kristiyandaru, Advendi; Nurhasan, Nurhasan; Muhammad, Heryanto Nur; Kartiko, Dwi Cahyo; Indriarsa, Nanang (JOSSAE (Journal of Sport Science and Education), 2022)
This study aims to identify online learning conducted by physical education teachers among public senior high schools in Surabaya. The approach used in this research is a quantitative approach. The population in this study are sports teachers at SMA Negeri in Surabaya. Then, the sample was taken with purposive sampling where one school selected one sports teacher only. The data collection is done online and allocated for one month, namely in the month from September 15th to October 10th, 2020. The identification stages include the evaluation of the preparation stage, the evaluation of the implementation stage, the evaluation of the assessment stage, and the evaluation of the post-learning online. The results showed that more than 52% of respondents had designed and developed RPP under the Covid-19 pandemi conditions, 100% of them "agreed" to carry out learning based on the school schedule, and all aspects of learning covering cognitive, psychomotor, and affective aspects had been implemented.